Light-induced modulation of DNA recognition by the Rad4/XPC damage sensor protein. Issue 2 (6th January 2021) - Tavakoli, Amirrasoul; Paul, Debamita; Mu, Hong; Kuchlyan, Jagannath; Baral, Saroj; Ansari, Anjum; Broyde, Suse; Min, Jung-Hyun
Abstract : Rad4/XPC DNA damage sensor protein specifically binds to a photocleavable NPOM-DNA adduct, and this recognition is abolished upon photo-cleavage of NPOM. Abstract : Biomolecular structural changes upon binding/unbinding are key to their functions. However, characterization of such dynamical processes is difficult as it requires ways to rapidly and specifically trigger the assembly/disassembly as well as ways to monitor the resulting changes over time. Recently, various chemical strategies have been developed to use light to trigger changes in oligonucleotide structures, and thereby their activities. Here we report that photocleavable DNA can be used to modulate the DNA binding of the Rad4/XPC DNA repair complex using light. Rad4/XPC specifically recognizes diverse helix-destabilizing/distorting lesions including bulky organic adduct lesions and functions as a key initiator for the eukaryotic nucleotide excision repair (NER) pathway. We show that the 6-nitropiperonyloxymethyl (NPOM)-modified DNA is recognized by the Rad4 protein as a specific substrate and that the specific binding can be abolished by light-induced cleavage of the NPOM group from DNA in a dose-dependent manner. Fluorescence lifetime-based analyses of the DNA conformations suggest that free NPOM-DNA retains B-DNA-like conformations despite its bulky NPOM adduct, but Rad4-binding causes it to be heterogeneously distorted. Subsequent extensive conformational searches and molecular dynamics simulations demonstrate that NPOM in DNA can be housed in the major groove of the DNA, with stacking interactions among the nucleotide pairs remaining largely unperturbed and thus retaining overall B-DNA conformation. Our work suggests that photoactivable DNA may be used as a DNA lesion surrogate to study DNA repair mechanisms such as nucleotide excision repair.